2010
DOI: 10.1159/000297602
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal Distribution of <i>PAX6</i> and <i>MEIS2</i> Expression and Total Cell Numbers in the Ganglionic Eminence in the Early Developing Human Forebrain

Abstract: The development of the human neocortex is a complex and highly regulated process involving a time-related expression of many transcription factors including the homeobox genes Pax6 and Meis2. During early development, Pax6 is expressed in nuclei of radial glia cells in the neocortical proliferative zones and controls the differentiation and neurogenetic fate of these cells in the dorsal telencephalon in rodents. Animal studies on the Meis2 gene have revealed expression in the developing telencephalon and Meis2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(27 citation statements)
references
References 135 publications
(81 reference statements)
3
24
0
Order By: Relevance
“…Meis1 was reported to be expressed in the caudal ganglionic eminence in mouse (Toresson et al, 2000), but XMeis1 is absent in the Xenopus forebrain (Maeda et al, 2002). Similar to our observation in chicken, striatal and pallial Meis2 expression was observed in the developing mouse (Toresson et al, 1999(Toresson et al, , 2000, monkey (Takahashi et al, 2008), and human forebrain (Larsen et al, 2010), and was described as possibly ''basal ventral telencephalon expression'' in zebrafish (Zerucha and Prince, 2001;Biemar et al, 2001). This partial evidence about conserved expression patterns, added to the postulated retinoid signals necessary to obtain striatal and ventral pallial Meis2-related derivatives in chicken, and to the evidence of Meis2 as a potential upstream modulator of mouse Dlx genes, suggests an early role for Meis genes in the complex telencephalic patterning process (Marklund et al, 2004;Ghanem et al, 2008).…”
Section: Meis Gene Expression From Neural Tube Closure To Hh20 Stagessupporting
confidence: 88%
See 1 more Smart Citation
“…Meis1 was reported to be expressed in the caudal ganglionic eminence in mouse (Toresson et al, 2000), but XMeis1 is absent in the Xenopus forebrain (Maeda et al, 2002). Similar to our observation in chicken, striatal and pallial Meis2 expression was observed in the developing mouse (Toresson et al, 1999(Toresson et al, , 2000, monkey (Takahashi et al, 2008), and human forebrain (Larsen et al, 2010), and was described as possibly ''basal ventral telencephalon expression'' in zebrafish (Zerucha and Prince, 2001;Biemar et al, 2001). This partial evidence about conserved expression patterns, added to the postulated retinoid signals necessary to obtain striatal and ventral pallial Meis2-related derivatives in chicken, and to the evidence of Meis2 as a potential upstream modulator of mouse Dlx genes, suggests an early role for Meis genes in the complex telencephalic patterning process (Marklund et al, 2004;Ghanem et al, 2008).…”
Section: Meis Gene Expression From Neural Tube Closure To Hh20 Stagessupporting
confidence: 88%
“…In the chicken midbrain, expression of Meis1/2 was confirmed (Ferran et al, 2007, Agoston andBobak et al, 2009;Coy and Borycki, 2010), as also observed in Xenopus (Maeda et al, 2001(Maeda et al, , 2002, zebrafish (Biemar et al, 2001;Waskiewicz et al, 2001;Zerucha and Prince, 2001), mouse (Cecconi et al, 1997;Oulad-Abdelghani et al, 1997;Shim et al, 2007), and human (Larsen et al, 2010). Our isoform analysis by RT-PCR showed that Meis2A.1 is slightly more expressed in the chicken during development and postnatal stages.…”
Section: Meis Gene Expression From Neural Tube Closure To Hh20 Stagessupporting
confidence: 81%
“…Meis2 maps to human chromosome 15 ( 36 ), but, except for its involvement in developmental processes and cancer (37)(38)(39), not much is known about the function of this transcription factor. Although our transfection experiments revealed that Meis2d acts as a positive regulator of both the hepatic and intestinal SOAT2 expression ( Fig.…”
Section: Discussionmentioning
confidence: 99%
“…MEIS2 was present in the proliferative zones of the human fetal neocortex and in the developing ganglionic eminence and at a more moderate level in the cortical plate [Larsen et al, 2010]. In a recent genome-wide pharmacogenomic study of metabolic side effects to antipsychotic drugs the top finding in 738 schizophrenia patients was at the MEIS2 locus, where intronic SNP rs1568679 mediated the effects of risperidone on hip and waist circumference [Adkins et al, 2011].…”
Section: à5mentioning
confidence: 99%